Edukasi Pengobatan Gastritis Melalui Pemanfaatan Obat Herbal - Dewi, Rasmala; Fadilla, Nurul; Aldilas, Wahyu Tri; Rosita, Mia; Pinasty, Afifah Putri; Khodijah, Siti Ayu; Zalita, Tricy Opi; Nurhikmah, Nurhikmah (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Gastritis is a condition of inflammation or bleeding of the gastric mucosa which can be acute and chronic. People generally know gastritis as ulcer disease, which is a disease that according to them is not a big problem, gastritis occurs at all ages, from children, adolescents, adults to old people. Gastritis is a condition of inflammation of the gastric mucosa which is can be acute and chronic due to lack of patient attention to health, one of which is the adoption of an unhealthy lifestyle. The purpose of this research is to find out the education of gastritis treatment through the use of herbal or natural medicines. The research method used is a qualitative research method using an information gathering design on issues specifically designed to study in detail and in depth the use of herbal medicine in overcoming gastritis.